«Semi-Renovationism» in the Patriarch Tikhon Church in the Middle of 1920s: Bishop Iacov (Mascaev) at Orenburg cathedra (1923–1925) - Zimina Nina (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2014)
The article is devoted to analysis of Church politics of Bishop Iacov (Maskaev) at the Orenburg cathedra in 1923–1925. It is shown that before his consecration, Iacov Maskaev supported the dual tactics of the Orenburg Bishop Aristarch (Nickolaevsky), which recognized the schismatic Supreme Ecclesiastical Administration, but opposed the activities of the renovationist authorized representative on imposition of a schism. In this regard, the consecration of Iacov (Maskaev) to the Orsk vicar cathedra in March 1923 was considered as an important step in strengthening of Episcopal authority in the Orenburg diocese in contrast to the tactics of schismatics. However, the question about validity of his consecration, performed by renovationist bishops, was fi nally resolved only in October 1923, when Patriarch Tikhon recognized Iacov as the Bishop of Orsk and appointed him a temporary administrator of the Orenburg diocese. At the same time, under the pressure of the OGPU Bishop Iacov gave a covert subscription about submission to the renovationist «synod» and received its decree, dated November 1923, on the appointment the ruling Orenburg Bishop. This decree was not announced in the diocese. Thus, Bishop Iacov became «the secret schismatic», although went on to declare himself the Orthodox hierarch. In the autumn of 1923 Bishop Iacov issued a declaration outlining his new, “Semi-Renovationist” Church platform, including distancing from the “counterrevolutionary” politics of Patriarch Tikhon, administrative ubordination to the Renovationist “synod” when saving the canonical obedience to the Patriarch, Church reforms, consolidation with schismatics. The result of politics of Bishop Iacov (Maskaev) became the legalization of the Orenburg Diocesan administration in December 1923. The period of “Secret Renovationism” of Bishop Iacov was completed in January 1925, when he was banned from serving, dismissed from the Department and repressed for the rejection an open transition into schism. The analysis of the activity of Bishop Iacov has allowed to conclude that the main purpose of his Church policy, very controversial in the canonical respect, was the legalization of diocesan administration while maintaining the canonical and covert administrative ties with Patriarch Tikhon. The “Declaration” of Bishop Iacov (Maskaev) opened a period in Church history, related with “Semi-Renovationist” policy of many bishops who tried to settle the legal status of the dioceses through serious compromises with the civil authorities. This period was over in 1927 with the wellknown “Declaration” of Metropolitan Sergey (Stragorodsky) on behalf of the entire Russian Church.